METODOLOGI PENELITIAN KRISTOLOGI DAN KRITERIA KEASLIAN DALAM STUDI YESUS SEJARAH - Desti; Yulpana (Adisam Publisher, 2026)
This study examines Christological methodology as an approach to understanding the person and work of Jesus Christ in their entirety, encompassing both His divine and human natures. Based on biblical studies, this method involves various approaches such as historical-critical, theological, literary, and interdisciplinary methods to achieve a balanced and profound understanding. This study also outlines criteria of authenticity in historical Jesus research, which include the criteria of double attestation, anomalies, inconsistencies, continuity, and coherence. The application of these criteria demonstrates that Jesus’ teachings and actions possess a strong foundation of authenticity, supported by numerous sources and objective analysis, although they remain limited due to their reliance on human interpretation and academic rationality. Therefore, criteria of authenticity should be regarded as tools, not as the primary foundation, so that Christological studies continue to balance scientific and faith-based dimensions. In the context of contemporary life, a correct understanding of Jesus Christ through Christological methodology can help believers to emulate Christ’s love, obedience, and moral values in a tangible way, whether in personal life, church ministry, or social roles within society.